One-Pot Synthesized Nickel-Cobalt Sulfide-Decorated Graphene Quantum Dot Composite for Simultaneous Electrochemical Determination of Antiretroviral Drugs: Lamivudine and Tenofovir Disoproxil Fumarate - Chihava, Ruvimbo; Apath, Daniel; Moyo, Mambo; Shumba, Munyaradzi; Chitsa, Vitalis; Tshuma, Piwai (Hindawi Limited, 2021)
In the present study, simultaneous electrochemical behavior of tenofovir disoproxil fumarate (TDF) and lamivudine (LAM) on a glassy carbon electrode (GCE) modified with a novel nanocomposite, nickel-cobalt sulfide-decorated graphene quantum dots (Ni-CoS/GQDs) was investigated. Characterization of different components used for modifications was achieved using UV-Vis and transmission electron microscopy (TEM). The electrochemistry of TDF and LAM at the modified electrode was examined using cyclic voltammetry (CV), linear sweep voltammetry (LSV), chronoamperometry, differential pulse voltammetry (DPV), and electrochemical impedance spectroscopy (EIS). A substantial (+39 mV TDF; +20 mV LAM) decrease in potential on oxidation reaction in 0.1 M PBS (pH 8.0) was achieved due to synergy between Ni-CoS and GQDs. Using optimized voltammetric parameters and pH, DPV gave a linear calibration over the range 5-18 μM for TDF and LAM. The detection limits were calculated as  mM (LAM) and  mM (TDF). The estimated values for Gibbs free energy revealed adsorption of TDF and LAM on Ni-CoS/GQDs/GCE as a spontaneous and favorable process. The voltammetric method was applied for determination of LAM and TDF in a pharmaceutical formulation giving average recovery of 99.65%.